Analisis Pendapatan dan Kelayakan Usaha Jamur Tiram pada Usahatani Jamur Simbang di Desa Simbang Kecamatan Simbang Kabupaten Maros - Misnatussada Tunnisa; Azisah Azisah; Abd. Asis Pata (Jurnal Agribis, 2026)
This study aims to: (1) determine the income from oyster mushroom farming at Usahatani Jamur Simbang in Simbang Village, Simbang Sub-district, Maros Regency; and (2) assess the feasibility of the oyster mushroom farming business. The research was conducted at Usahatani Jamur Simbang, located in Simbang Village, Simbang Sub-district, Maros Regency, over a period of four months, from February to May 2025. A quantitative descriptive analysis method was used to examine the income and business feasibility. Data were collected through surveys, field observations, and questionnaires. The sampling method used was purposive sampling, selecting active farmers who had completed at least one full production cycle. The data were analyzed using total cost, revenue, net income, and R/C Ratio calculations. The results showed that the net income obtained by Usahatani Jamur Simbang was IDR 15,757,690. The feasibility analysis revealed an R/C Ratio value of 1.78, indicating that the oyster mushroom farming business is financially feasible to pursue.